FACTORS THAT AFFECTING THE DELAY OF BUDGET ABSORPTION AT DIRECTORATE GENERAL OF EDUCATION OF EARLY CHILDHOOD AND COMMUNITY EDUCATION - Henry, Julian Sembiring (International Journal of Public Budgeting, Accounting and Finance, 2018)
This study aims to examine and to analyze the effect of planning, administration, government internal control officer (APIP) and regulation simultaneously and partially to the delay of budget absorption at Directorate General of Early Childhood Education and Community Education (Ditjen PAUD Dikmas) with the budget administrator culture as a moderator variable. The type of research used is survey research. The population in this study is 27 commitment making officials (PPK), 13 treasurers of expenditure and 13 budget compilers in all work unit in Ditjen PAUD Dikmas. The sampling method is census technique because all the population used as the sample amounted to 53 samples. The data used in this study is the primary data. The analysis method used is multiple linear regression analysis and residual test. The results of this study indicate that planning, administration, APIP and regulation have a significant effect on the delayed of budget absorption simultaneously. Partially planning, administration and regulation have significant effect on the delay of budget absorption while APIP has no effect. The budget administrator culture cannot moderate the relationship between planning, administration, APIP and regulations with the delay of Ditjen PAUD Dikmas’ budget absorption